(3cJGH aj PcQ HYV GdCOhjI Ch GdYdGLs - (3Chaj Hf CHj HcQ GdCdabj GdTeThj,J (B1300 (3g` s
(3ChdgG (B:s
(3bGd TjN GdCWHGA Chai ai PcQ HYV GdCOhjI Ch GdYdGL Ef hLY GdXgQ YdGLI GdHhd bGFekG hGdHUGb hdMe GdLOi heG ONd ai GdCPf YdGLI s
(3BNQgG (B:s
(3gPG MGUd eG QGjfG ai GdcJH hJdjbfGg ef GdCTjGN , hf QCi NdGa Pdc adjJFO , dYdg ehGab deG PcQ , Ch NdGa GdeTghQ , hGdSdGe s
(3HgG fXGe GdJYbjHIs
(3fSNI JGeI eQeeIs
(3efbhdI ef NW GdTjN jMXjg Hf YHO GdhOhO ef GdbQf (B13 (3g` s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , JQeje s
Keywords: (3GdWHs